Discriminatory matrix for the larvae of the European Thremma species (Trichoptera: Thremmatidae) - Waringer, Johann; González, Marcos A.; Malicky, Hans (Zootaxa, 2020)
This synoptic paper is intended to summarize and supplement the information available on the larvae of Thremma McLachlan 1876 in Europe. We present information on the morphology of the larvae and illustrate the most important diagnostic features. This information is used for the construction of a comprehensive discriminatory matrix for the four European species of family Thremmatidae Martynov 1935 known in the larval stage so far. In the context of this matrix, larvae can be easily diagnosed by the shape of mesonotal sclerites, foretrochantins, forefemora and ventral sclerites on abdominal segment I, by head coloration patterns, by case morphology, and by distribution. In addition, ecological characteristics and distributions of the European taxa are briefly discussed.